The Analysis of Speech Function in Prabowo’s Inaguration Speech - Linda Efrina Nasution; Masria Sari Pasaribu (Journal Of Language Education and Development (JLed), 2026)
This study investigates the speech functions employed in Prabowo Subianto's inaguration speech using Halliday's Systemic Functional Linguistics (SFL) framework. The objective of the study is to identify the dominant speech functions and explain how these functions contribute to the effectiveness of political communication. A qualitative descriptive method was employed by analyzing the clauses contained in one selected speech delivered by Prabowo Subianto. The data were categorized into four speech function types: Statement, Question, Command, and Offer. The findings indicate that Statement is the most dominant speech function, followed by Command, while Question and Offer occur less frequently. The predominance of declarative statements demonstrates Prabowo's intention to inform, persuade, and establish credibility before his audience. Meanwhile, commands function as motivational devices encouraging collective action. The study concludes that speech functions play a significant role in constructing political authority, strengthening leadership identity, and influencing public perception.